Application of Batch Electrocoagulation for Pollutant Removal in Tapioca Wastewater: An Environmental Engineering Approach for Sustainable Water Treatment Solutions - Fajar, Mutiara; Putra, Afrinaldi; Munandar, Andika; Lutfi Setia Putri, Shabrina; Utami, Resarizki (Dampak, 2024)
Tapioca wastewater is rich in organic compounds, leading to high levels of COD (Chemical Oxygen Demand) and TSS (Total Suspended Solids). When these concentrations exceed regulatory standards, they can cause significant water pollution, which may indirectly affect human health. Therefore, it is essential to treat tapioca wastewater before discharging it into water bodies. Electrocoagulation is a promising treatment method for this purpose, as it can effectively remove contaminants through coagulation, separation, and sedimentation of fine particles using electrical energy. This study evaluated the efficiency of COD and TSS removal from tapioca wastewater using an aluminium electrode with voltage variations of 10, 20, and 30 volts. Initial concentrations of COD and TSS in the untreated wastewater were measured at 641 mg/L and 382 mg/L, respectively. Optimal removal rates were achieved at 20 volts, with reduction efficiencies of 79.5% for COD and 82.7% for TSS. Statistical analysis using ANOVA indicated a significant impact of voltage variations on COD and TSS removal efficiency, with a p-value < 0.05 and an F-value greater than the critical F-value. These findings demonstrate that electrocoagulation, particularly at an optimal voltage of 20 volts, effectively reduces the COD and TSS levels in tapioca wastewater, suggesting its potential application as an environmentally friendly solution for industrial wastewater treatment.